Rehabilitation Outcomes: Ischemic versus Hemorrhagic Strokes - Robert Perna; Jessica Temple (Behavioural Neurology)
Background. Ischemic and hemorrhagic strokes have different pathophysiologies and possibly different long-term cerebral and functional implications. Hemorrhagic strokes expose the brain to irritating effects of blood and ischemic strokes reflect localized or diffuse cerebral vascular pathology. Methods. Participants were individuals who suffered either an ischemic (n=172) or hemorrhagic stroke (n=112) within the past six months and were involved in a postacute neurorehabilitation program. Participants completed three months of postacute neurorehabilitation and the Mayo Portland Adaptability Inventory-4 (MPAI-4) at admission and discharge. Admission MPAI-4 scores and level of functioning were comparable. Results. Group ANOVA comparisons show no significant group differences at admission or discharge or difference in change scores. Both groups showed considerably reduced levels of productivity/employment after discharge as compared to preinjury levels. Conclusions. Though the pathophysiology of these types of strokes is different, both ultimately result in ischemic injuries, possibly accounting for lack of findings of differences between groups. In the present study, participants in both groups experienced similar functional levels across all three MPAI-4 domains both at admission and discharge. Limitations of this study include a highly educated sample and few outcome measures.